Active Operation and Maintenance Platform for Information System Based on User Experience - Shun Wu; Dawei Xu; Zheng Wei; Chengchen Hu; Wanhong Xiang; Qian Guo; Yazhe Tang (Dianxin kexue)
The traditional monitoring maintenance system only watches the running metrics.However,these metrics is not sufficient to reflect the status of the whole system for fine-grained monitoring of the system at users and application level.An active operation and maintenance platform based on user experiences was proposed.Through the mining of big network data,the platform can recognize a variety of user behaviors,and measure the user experience time along with the system performance at user's level.Tests and experiments show that the platform works well with large throughput and low memory occupation.The application level performance monitoring,which provides an efficient way to improve user experience,was realized.